The Influence of Parenting Style and Teacher's Teaching Style on Student Learning Independence - Anayanti, Dinda Kestu; Zainuddin, Almuntaqo (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study used a quantitative approach to analyze the influence of parenting styles and teaching methods on students' learning independence. All fifth-grade students at the school constituted the study population, with a sample of 20 students selected using a saturated sampling technique. Data collection was conducted using questionnaires, while data analysis was carried out using multiple linear regression. The results show that parenting styles have a greater impact (t = 5.155, p < 0.05) than teaching styles (t = 2.780, p < 0.05). The F-test confirms a significant combined effect (F = 12.917, p < 0.0001), with an R² value of 0.618, indicating that 61.8% of learning independence is explained by these variables. The findings highlight the importance of democratic parenting and interactive teaching in fostering student autonomy. Collaboration between parents and teachers is essential for maximizing learning independence.